Integrating Computer Literacy and Social Skills in Maritime Education: Enhancing Cadet Readiness - Panderaja Soritua Sijabat; April Gunawan Malau; Mudakir Mudakir; Wardoyo Dwi Kurniawan; Meriyanti Agustinawati (Dinasti International Journal of Education Management And Social Science, 2024)
This research investigates the integration of computer literacy and social skills within Maritime Institute programs, focusing on the readiness of cadets for the contemporary maritime industry. Through qualitative analysis of 30 graduates from Sekolah Tinggi Ilmu Pelayaran Jakarta and quantitative data collection, the study elucidates the importance of these competencies in navigating the dynamic challenges of the maritime sector. Findings reveal a consensus among participants regarding the critical role of computer literacy, while variability exists in the perceived integration of social skills within curricula. Additionally, the research identifies research needs, dimensions of professionalism, and alignment with international standards, providing insights for education management and professionalism in the maritime industry. By addressing these challenges and opportunities, Maritime Institute programs can better prepare graduates for the demands of the global maritime marketplace, contributing to the advancement of the sector and ensuring the competitiveness of future maritime professionals.